Use of steroids to treat anti-tumor necrosis factor α induced tuberculosis-associated immune reconstitution inflammatory syndrome: Case report and literature review. Issue 43 (23rd October 2020) - Nabeya, Daijiro; Kinjo, Takeshi; Yamaniha, Kazutaka; Yamazato, Shoshin; Tome, Reo; Miyagi, Kazuya; Nakamura, Hideta; Kinjo, Tetsu; Haranaga, Shusaku; Higa, Futoshi; Fujita, Jiro
Abstract: Introduction: Individuals with tuberculosis (TB) who are being treated with anti-tumor necrosis factor α (anti-TNFα) for coexisting conditions may experience unexpected exacerbations of TB after the initiation of antituberculous therapy, so-called anti-TNFα-induced TB-immune reconstitution inflammatory syndrome (anti-TNFα-induced TB-IRIS). Anti-TNFα-induced TB-IRIS is often treated empirically with corticosteroids; however, the evidence of the effectiveness of corticosteroids is lacking and the management can be a challenge. Patient concerns: A 32-year-old man on long-term infliximab therapy for Crohn disease visited a clinic complaining of persistent fever and cough that had started 1 week previously. His most recent infliximab injection had been administered 14 days before the visit. A chest X-ray revealed a left pleural effusion, and he was admitted to a local hospital. Diagnosis: A chest computed tomography (CT) scan revealed miliary pulmonary nodules; acid-fast bacilli were found in a sputum smear and a urine sediment sample; and polymerase chain reaction confirmed the presence of Mycobacterium tuberculosis in both his sputum and the pleural effusion. He was diagnosed with miliary TB. Interventions: Antituberculous therapy was started and he was transferred to our hospital for further management. His symptoms initially improved after the initiation of antituberculous therapy, but 2 weeks later, his symptoms recurred and shadows on chest X-ray worsened. A repeat chest CT scan revealed enlarged miliary pulmonary nodules, extensive ground-glass opacities, and an increased volume of his pleural effusion. This paradoxical exacerbation was diagnosed as TB-IRIS associated with infliximab. A moderate-dose of systemic corticosteroid was initiated [prednisolone 25 mg/day (0.5 mg/kg/day)]. Outcomes: After starting corticosteroid treatment, his radiological findings improved immediately, and his fever and cough disappeared within a few days. After discharge, prednisolone was tapered off over the course of 10 weeks, and he completed a 9-month course of antituberculous therapy uneventfully. He had not restarted infliximab at his most recent follow-up 14 months later. Conclusion: We successfully managed a patient with anti-TNFα-induced TB-IRIS using moderate-dose corticosteroids. Due to the limited evidence currently available, physicians should consider the necessity, dosage, and duration of corticosteroids for each case of anti-TNFα-induced TB-IRIS on an individual patient-by-patient basis.